Variation versus Permanence in 46 Years of Hypological Lexicon - Groba Bouza, Fernando (Madrygal. Revista de Estudios Gallegos, 2023)
The main objective of this article is to analyze the linguistic change at the social and geographical level in oral Galician of 71 denominative units that belong to three thematic subareas in the field of hypology: denomination of horses, body parts and vital actions. To do this, it groups and contrasts the dialectal information, the number of records and the percentages of frequency of use of different denominations shared by the doctoral thesis O léxico da hipoloxía no galego oral and the database that served as a source of information for its realization with two works elaborated in two previous moments: the Glosario de voces galegas de hoxe and the Atlas lingüístico galego. These are three studies that provide, as a whole, geolinguistic lexicological information on a network that has a total of 319 different geographical points in a time span that spans almost half a century. As a result, despite the differences between the three works in terms of type of authorship, sources, objectives, scope and field of study, the versatility and immense value of their data is demonstrated to assess and observe how they all increase, decrease or maintain each and everyone of the denominations they have in common.